Singapore : Financial Sector Assessment Program; Technical Note-Financial Stability Analysis and Stress Testing. (IMF Staff Country Reports; Country Report, 2019)
This technical note Financial Stability Analysis and Stress Testing on Singapore contributes to the assessment of the stability and soundness of the financial sector with a comprehensive set of risk analyses. The work combines an examination of key risk indicators with detailed stress tests, which simulate the health of banks, insurers, nonfinancial corporates and households under severe yet plausible (counterfactual) adverse scenarios. Scenarios include global financial market turmoil, a major slowdown of economic activity in China, cyber-attacks and extreme flooding. The analyses include simulations of contagion within the international banking network, within the domestic banking system and between different types of financial institutions in the financial system. The stress tests reveal that the financial system is broadly resilient to severe adverse shocks; however, foreign exchange liquidity is a key vulnerability. The analyses suggest that Monetary Authority of Singapore should continue strengthening its surveillance by closing data gaps and developing its analytical tools. Further data collection on domestic interlinkages, household mortgage debt at the borrower level, insurers' balance sheets would enhance surveillance.